PO137 Efficacy of cladribine tablets in high disease activity rms. (1st December 2017) - Giovannoni, Gavin; Rammohan, Kottil; Cook, Stuart; Comi, Giancarlo; Rieckmann, Peter; Soelberg-Sorensen, Per; Vermersch, Patrick; Dangond, Fernando; Hicking, Christine
Abstract : Background: In the CLARITY study, treatment with cladribine tablets (CT) vs placebo showed strong efficacy in patients with RMS. Post-hoc analysis may provide insights into the efficacy of CT in patients with HDA. Objective: To compare the effects of CT 3.5 mg/kg (CT3.5) vs placebo using two HDA definitions. Methods: Patients randomised to CT3.5 (n=433) or placebo (n=437) were analysed using two HDA definitions based on high relapse activity ([HRA]≥2 relapses in the previous year) regardless of prior treatment, or a HRA plus treatment nonresponse ([HRA +TNR]≥2 relapses in the previous year, or ≥1 relapse in previous year while on DMD therapy and ≥1 T1 Gd +or ≥9 T2 lesions). Results: In the overall population, CT3.5 reduced risk of 6 month EDSS progression by 47% (HR=0.53, 95%CI:0.36;0.79) vs placebo. A larger risk reduction for CT3.5 vs placebo of 82% was seen in the HRA and HRA +TNR subgroups (HR=0.18 each, 95%CI:0.08;0.44 and 0.07;0.43). ARR was lower with CT3.5 than placebo in the overall population (RR=0.42, 95%CI:0.33;0.52), and even lower for HRA (RR=0.32, 95%CI:0.22;0.47) and HRA +TNR (RR=0.33;95% CI:0.23;0.48). Conclusions: Patients identified by HDA criteria showed clinical and MRI responses to CT3.5 that were generally better than, or at least comparable with, outcomes in the overall CLARITY population.